2021
DOI: 10.1002/cbdv.202100638
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents of the Essential oil fromCuminum cyminumL. and Its Antifungal Activity againstPanax notoginsengPathogens

Abstract: Cuminum cyminum L. (Cumin) is a flavoring agent that is commonly used worldwide, and is rich in essential oil. Essential oils (Eos) have been intensively investigated in regard to their potential for disease control in plants, which is provided a chance for the blossom of green pesticides. The chemical components of Cumin essential oil (CEO) were revealed by GC/MS, such as cuminaldehyde (44.53 %), p-cymene (12.14 %), (À )-β-pinene (10.47 %) and γ-terpinene (8.40 %), and found they can inhibit the growth of P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Thymus zygis (red thyme) essential oil possesses a broad antimicrobial spectrum and may even enhance the effect of certain antimicrobial agents [35]. The chemical components of cumin essential oil can inhibit the growth of Panax notoginseng-associated pathogenic fungi in vitro, and the inhibitory effect of cuminaldehyde was similar to that of hymexazol [36]. These studies verified the potential of plant essential oil as a plant insecticide, fungicide, and herbicide that is environmentally friendly and provide ideas for developing new products to control agricultural pests.…”
Section: Discussionmentioning
confidence: 99%
“…Thymus zygis (red thyme) essential oil possesses a broad antimicrobial spectrum and may even enhance the effect of certain antimicrobial agents [35]. The chemical components of cumin essential oil can inhibit the growth of Panax notoginseng-associated pathogenic fungi in vitro, and the inhibitory effect of cuminaldehyde was similar to that of hymexazol [36]. These studies verified the potential of plant essential oil as a plant insecticide, fungicide, and herbicide that is environmentally friendly and provide ideas for developing new products to control agricultural pests.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have provided evidence supporting the antidiabetic effects of CC's essential oil [20]. The active components of this plant include Cumin aldehyde (approximately 49.4%), α-terpinen-7-al (6.8%), β-pinene (6.3%), g-Terpinene (6.1%), γ-terpinene (6.1%), p-cymen-7-ol (4.6%) and thymol (2.8%) [21]. Among these components, Cumin aldehyde, also known as 4-isopropyl Benzaldehyde, exhibits the most potent activity.…”
Section: Introductionmentioning
confidence: 89%
“…Moreover, other plant EOs, such as Mentha haplocalyx and Schizonepeta tenuifolia (Chen et al, 2020), Pogostemon cablin (Li, Huo, et al, 2020), Eupatorium fortunei (Li, Huo, et al, 2020), TA B L E 1 The function of beneficial microorganisms as biocontrol agents in root rot of Panax notoginseng. Cymbopogom citratus (Yang, Li, Huo, et al, 2022), Syzygium aromaticum and Cuminum cyminum (Huo et al, 2021), have been reported to have antifungal activity against pathogens of P. notoginseng. Liu et al (2021) revealed that the application of allyl isothiocyanate, in the volatiles of Brassica juncea, inhibits the growth of root rot pathogens of P. notoginseng by inducing ROS accumulation.…”
Section: Plant Secondary Metabolitesmentioning
confidence: 99%
“…( 2019 ) revealed that Cinnamomum cassia EOs possess antimicrobial activity against a variety of pathogens of P. notoginseng . Moreover, other plant EOs, such as Mentha haplocalyx and Schizonepeta tenuifolia (Chen et al., 2020 ), Pogostemon cablin (Li, Huo, et al., 2020 ), Eupatorium fortunei (Li, Huo, et al., 2020 ), Cymbopogom citratus (Yang, Li, Huo, et al., 2022 ), Syzygium aromaticum (Ma, Xu, Chen, Li, et al., 2019 ) and Cuminum cyminum (Huo et al., 2021 ), have been reported to have antifungal activity against pathogens of P. notoginseng .…”
Section: Biological Control Of Root Rot In P Notoginsengmentioning
confidence: 99%